Protein structure prediction problem: formalization using quaternions - Hulianytskyi, L. F.; Rudyk, V. O. (Cybernetics and systems analysis, 2013)
The authors discuss the formalization of protein tertiary structure prediction problem based on Dill’s HP-model. Three-dimensional discrete lattices and different approaches to representing paths on them are the subjects of investigation. Two ways of path encoding are proposed and formalized, one of which is based on quaternions.